(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2023)
Different disorders and physiological process have been found to be associated with monoacylglycerol lipase enzyme in humans, like pain, inflammation, and neurodegenerative diseases also. The enzyme is a 33 KDa in weight and a type of serine hydrolase enzyme in nature. The presence of enzyme has been reported in both central and peripheral nervous systems and has show its importance as a key signalling factor in endocannabinoid signalling network system. The enzyme has also reported as source of free fatty acid provider for the cancer cell and tumour growth and their proliferation. In proliferative cancer cells, increased the monoacylglycerol lipase activity is observed. The growth, migration and survival of cancer cells have also found to be associated with phosphatidic acid, lysophosphatidic acid, sphingosine phosphate and prostaglandin E2, which are act as signalling molecules and are found to be derived from free fatty acid. These are also found to be related to the growth, transmission and viability of cancer cells, which increases with the enzyme activity. In the present study we performing computation screening studies of newly designed monoacylglycerol inhibitors which contains carbamate features, these molecules are designed based on previously developed monoacylglycerol carbamate inhibitors.